2019
DOI: 10.1149/2.0311911jes
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Trace H2S on the Scale Formation Behavior in a Predominant CO2 Environment under Hydrodynamic Control: Role of Cr/Mo Micro-Alloying in Plain Carbon Steel

Abstract: The effects of the presence of trace H 2 S (∼ 0.5 μM total dissolved H 2 S) on the electrocrystallization of siderite on plain carbon steel and its various micro-alloyed counterparts are explored. This small concentration of H 2 S in a CO 2 saturated (sweet) brine (0.5 M NaCl), at 80°C, in a slightly acidic environment (pH 6.6) at the elevated temperature was found to increase the anodic dissolution rate of the plain carbon steel and inhibit the electrocrystallization of carbonate scale. Highly porous surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In earlier work we have presented detailed studies of anodic electrocrystallisation of iron carbonate layers on carbon steel at elevated temperature in CO2 containing solution [2][3][4][5][6][7][8][9][10][11][12]. We used both insitu synchrotron X-ray diffraction, and ex-situ measurement using a rotating disc electrode to control hydrodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier work we have presented detailed studies of anodic electrocrystallisation of iron carbonate layers on carbon steel at elevated temperature in CO2 containing solution [2][3][4][5][6][7][8][9][10][11][12]. We used both insitu synchrotron X-ray diffraction, and ex-situ measurement using a rotating disc electrode to control hydrodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The microstructure of steel plays a key role in determining its mechanical, structural, as well as chemical and electrochemical degradation properties, e.g., corrosion resistance [1][2][3][4][5][6][7][8][9]. Precisely the same materials chemistry with different microstructure provides a very different set of local properties [2,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The brine solution, containing CO 2 and H 2 S, is a corrosive medium, which accelerated localised corrosion such as pitting corrosion and sulphide stress corrosion cracking [12][13][14][15][16][17][18][19][20][21]. To date, a couple of studies have been conducted with a focus on the role of trace H 2 S in corrosion of carbon steel in the CO 2 -saturated solution [20][21][22][23][24][25][26][27][28][29]. Some of these investigations showed that addition of trace H 2 S into the CO 2 -saturated solution reduced the corrosion rate of carbon steel at room temperature due to the formation of thin sulphide film [21][22][23], whereas other studies concluded oppositely [20,[24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…To date, a couple of studies have been conducted with a focus on the role of trace H 2 S in corrosion of carbon steel in the CO 2 -saturated solution [20][21][22][23][24][25][26][27][28][29]. Some of these investigations showed that addition of trace H 2 S into the CO 2 -saturated solution reduced the corrosion rate of carbon steel at room temperature due to the formation of thin sulphide film [21][22][23], whereas other studies concluded oppositely [20,[24][25][26][27][28][29]. These studies found that the addition of an amount of H 2 S in the CO 2 -saturated solution dramatically increased the corrosion rate of carbon steel at higher temperature with a partial pressure of CO 2 at 10-12 MPa [24,25].…”
Section: Introductionmentioning
confidence: 99%